Amine–borane complex-initiated SF5Cl radical addition on alkenes and alkynes - Gilbert, Audrey; Langowski, Pauline; Delgado, Marine; Chabaud, Laurent; Pucheault, Mathieu; Paquin, Jean-François (Beilstein Journal of Organic Chemistry, 2020)
The SF5Cl radical addition on unsaturated compounds was performed using an air-stable amine–borane complex as the radical initiator. This method showed to be complementary to the classic Et3B-mediated SF5Cl addition on alkenes and alkynes. A total of seven alkene and three alkyne derivatives were tested in the reaction, with yields ranging from 3% to 85%.
Keywords: amine-borane complex; pentafluorosulfanyl chloride; pentafluorosulfanyl substituent; radical addition; radical initiation

(untitled) - Silvey, G. A.; Cady, G. H. (J. Am. Chem. Soc., 1950)

(untitled) - Thayer, A. M. (Chem. Eng. News, 2006)

(untitled) - Matsuzaki, K.; Okuyama, K.; Tokunaga, E.; Saito, N.; Shiro, M.; Shibata, N. (Org. Lett., 2015)

(untitled) - Bassetto, M.; Ferla, S.; Pertusati, F. (Future Med. Chem., 2015)

(untitled) - Savoie, P. R.; Welch, J. T. (Chem. Rev., 2015)

(untitled) - Dalvit, C.; Ko, S. Y.; Vulpetti, A. (J. Fluorine Chem., 2013)

(untitled) - Sheppard, W. A. (J. Am. Chem. Soc., 1962)

(untitled) - Jackson, D. A.; Mabury, S. A. (Environ. Toxicol. Chem., 2009)

(untitled) - Sowaileh, M. F.; Hazlitt, R. A.; Colby, D. A. (ChemMedChem, 2017)

(untitled) - Welch, J. T.; Lim, D. S. (Bioorg. Med. Chem., 2007)

(untitled) - Wipf, P.; Mo, T.; Geib, S. J.; Caridha, D.; Dow, G. S.; Gerena, L.; Roncal, N.; Milner, E. E. (Org. Biomol. Chem., 2009)

(untitled) - Chia, P. W.; Brennan, S. C.; Slawin, A. M. Z.; Riccardi, D.; O'Hagan, D. (Org. Biomol. Chem., 2012)

(untitled) - Zhang, Y.; Wang, Y.; He, C.; Liu, X.; Lu, Y.; Chen, T.; Pan, Q.; Xiong, J.; She, M.; Tu, Z.; Qin, X.; Li, M.; et al. (J. Med. Chem., 2017)

(untitled) - Moraski, G. C.; Bristol, R.; Seeger, N.; Boshoff, H. I.; Tsang, P. S.-Y.; Miller, M. J. (ChemMedChem, 2017)

(untitled) - Mori, S.; Tsuemoto, N.; Kasagawa, T.; Nakano, E.; Fujii, S.; Kagechika, H. (Chem. Pharm. Bull., 2019)

(untitled) - Naclerio, G. A.; Abutaleb, N. S.; Onyedibe, K. I.; Seleem, M. N.; Sintim, H. O. (RSC Med. Chem., 2020)

Eur. Pat. Appl. - Banks, B. J. (Parasiticidal pyrazoles, 1999)

(untitled) - Lim, D. S.; Choi, J. S.; Pak, C. S.; Welch, J. T. (J. Pestic. Sci. (Tokyo, Jpn.), 2007)

WO Pat. Appl. - Kay, I. T.; Barton, J. E. D.; Collins, D. J.; Kowalczyk, B.; Mitchell, G.; Shribbs, J. M.; Cox, J. M.; Barnes, N. J.; Smith, S. C. (Herbicides, 1994)

Eur. Pat. Appl. - Alt, G. H.; Pratt, J. K.; Phillips, W. G.; Srouji, G. H. (Substituted thiazoles and their use as fungicides, 1990)

(untitled) - Zhang, G.; Lee, Y.-J.; Gautam, P.; Lin, C.-C.; Liu, C.-L.; Chan, J. M. W. (J. Mater. Chem. C, 2019)

(untitled) - Kirsch, P.; Bremer, M.; Heckmeier, M.; Tarumi, K. (Angew. Chem., Int. Ed., 1999)

(untitled) - Henwood, A. F.; Webster, J.; Cordes, D.; Slawin, A. M. Z.; Jacquemin, D.; Zysman-Colman, E. (RSC Adv., 2017)

(untitled) - Iida, N.; Tanaka, K.; Tokunaga, E.; Mori, S.; Saito, N.; Shibata, N. (ChemistryOpen, 2015)

(untitled) - Chan, J. M. W. (J. Mater. Chem. C, 2019)

(untitled) - Pal, A. K.; Henwood, A. F.; Cordes, D. B.; Slawin, A. M. Z.; Samuel, I. D. W.; Zysman-Colman, E. (Inorg. Chem., 2017)

Emerging Fluorinated Motifs: Synthesis, Properties and Applications - Beier, P. (Pentafluorosulfanylation of Aromatics and Heteroaromatics, 2020)

Emerging Fluorinated Motifs: Synthesis, Properties and Applications - Haufe, G. (Pentafluorosulfanylation of Aliphatic Substrates, 2020)

(untitled) - Aït-Mohand, S.; Dolbier, W. R., Jr (Org. Lett., 2002)

(untitled) - Dolbier, W. R., Jr; Aït-Mohand, S.; Schertz, T. D.; Sergeeva, T. A.; Cradlebaugh, J. A.; Mitani, A.; Gard, G. L.; Winter, R. W.; Thrasher, J. S. (J. Fluorine Chem., 2006)

(untitled) - Verma, R. D.; Kirchmeier, R. L.; Shreeve, J. M. (Adv. Inorg. Chem., 1994)

(untitled) - Sidebottom, H. W.; Tedder, J. M.; Walton, J. C. (Trans. Faraday Soc., 1969)

(untitled) - Uematsu, R.; Saka, C.; Sumiya, Y.; Ichino, T.; Taketsugu, T.; Maeda, S. (Chem. Commun., 2017)

(untitled) - Ollivier, C.; Renaud, P. (Chem. Rev., 2001)

(untitled) - Renaud, P.; Beauseigneur, A.; Brecht-Forster, A.; Becattini, B.; Darmency, V.; Kandhasamy, S.; Montermini, F.; Ollivier, C.; Panchaud, P.; Pozzi, D.; Scanlan, E. M.; Schaffner, A.-P.; et al. (Pure Appl. Chem., 2007)

(untitled) - Frankland, E. (J. Chem. Soc., 1862)

(untitled) - Székely, A.; Klussmann, M. (Chem. – Asian J., 2019)

Ullmann's Encyclopedia of Industrial Chemistry - Brotherton, R. J.; Weber, C. J.; Guibert, C. R.; Little, J. L. (Boron Compounds, 2000)

(untitled) - Staubitz, A.; Robertson, A. P. M.; Manners, I. (Chem. Rev., 2010)

(untitled) - Couturier, M.; Tucker, J. L.; Andresen, B. M.; Dubé, P.; Negri, J. T. (Org. Lett., 2001)

(untitled) - Marciasini, L. D.; Richard, J.; Cacciuttolo, B.; Sartori, G.; Birepinte, M.; Chabaud, L.; Pinet, S.; Pucheault, M. (Tetrahedron, 2019)

(untitled) - Guerrand, H. D. S.; Marciasini, L. D.; Gendrineau, T.; Pascu, O.; Marre, S.; Pinet, S.; Vaultier, M.; Aymonier, C.; Pucheault, M. (Tetrahedron, 2014)

(untitled) - Guerrand, H. D. S.; Vaultier, M.; Pinet, S.; Pucheault, M. (Adv. Synth. Catal., 2015)

(untitled) - Richard, J.; Birepinte, M.; Charbonnier, J. B.; Liautard, V.; Pinet, S.; Pucheault, M. (Synthesis, 2017)

(untitled) - Birepinte, M.; Liautard, V.; Chabaud, L.; Pucheault, M. (Chem. – Eur. J., 2020)

(untitled) - Birepinte, M.; Liautard, V.; Chabaud, L.; Pucheault, M. (Org. Lett., 2020)

(untitled) - Liautard, V.; Delgado, M.; Colin, B.; Chabaud, L.; Michaud, G.; Pucheault, M. (ChemRxiv, 2020)

Fr. Pat. Appl. - Delgado, M.; Michaud, G.; Colin, B.; Simon, F.; Fouquay, S.; Pucheault, M. (Procédé de polymérisation d’au moins un composé polymérisable par voie radicalaire, 2020)

Fr. Pat. Appl. - Michaud, G.; Simon, F.; Fouquay, S.; Liautard, V.; Pucheault, M.; Colin, B. (Procédé de polymérisation avec un complexe de borane-amine, 2019)

(untitled) - Gilbert, A.; Paquin, J.-F. (J. Fluorine Chem., 2019)